Student Math Circles: Building collaborative places of mathematical inquiry across grades - Bolognese, Chris; Shahani, Sonam (Ohio Journal of School Mathematics, 2017)
In this article, the authors provide an alternative to traditional math clubs through the formation and facilitation of a student math circle (SMC).  Student math circles are a community of students across different grades who engage in open-ended low floor, high ceiling tasks.  The authors provide history and motivation for SMCs as well as a few sample problems that have been used.  Additionally, benefits of an SMC model are provided.